The Poetry of the Margin in Hayreddin Barbaros ’ Memories - Dr. Sabah Gheraibia (Al-Qanṭara, 2024)
The margin is a fundamental unit in the construction of narrative text and an important theme in contemporary literary and critical studies. Poetry has trended in the manifestations of their interaction and opens up new prospects for understanding and analyzing literary texts in their different cultural and historical contexts. The scientific paper entitled " The Poetry of the Margin in Hayreddin Barbaros ' Memories " examined the value of these margins and their relationship to building and understanding the narrative of the texts of the memories " This study drew on the analytical curriculum and reached the following findings: The importance of margins in Hayreddin Barbaro's Memories is reflected in its role as a vital tool that promotes understanding of the text and provides additional context for the reader. Margins are used to explain cultural and historical terms that may be ambiguous, helping to clarify the exact meanings associated with the text's temporal and spatial context. Margins provide additional information on the events and personalities mentioned, which helps to understand the cultural and political interactions that took place during that period. Margins help guide the reader to other sources and references to explore topics more deeply Margins contribute to maintaining the scientific integrity of translated work in general